PENGARUH PENGGUNAAN YOUTUBE TERHADAP MINAT DAN MOTIVASI BELAJAR MATEMATIKA - Fitria Zana Kumala (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2021)
ABSTRACTInterest and motivation in learning are factors that greatly influence learning outcomes. This study aims to analyze the effect of Youtube videos on students’ interest and motivation in learning Mathematics at the State Islamic University of Prof. K.H. Saifuddin Zuhri Purwokerto by applying Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The variables used in this study are latent variables with the number of samples amounting to 160 samples. The analysis was carried out using SmartPLS 3.0 software. The findings revealed that Youtube videos had a significant direct positive effect on the students’ learning interest (p value = 0.000 0.05) with a path coefficient of 0.415, Youtube videos also had a significant direct positive effect on the students’ learning motivation (p value = 0.000 0.05) with a path coefficient of 0.260. The learning interest, on the other hand, had a significant direct positive effect on the students’ learning motivation (p value = 0.000 0.05) with a path coefficient of 0.529. Youtube videos had a significant indirect positive effect - through learning interest - on the students’ learning motivation (p value = 0.000 0.05) with a path coefficient of 0.220. Furthermore, the results showed that the total effect of YouTube videos on the students’ learning motivation is significant (p value = 0.000 0.05) with a path coefficient of 0.480. The effect of Youtube videos on the students’ learning interest is 16.7%, the remaining percentage is influenced by other variables. The effect of Youtube videos and learning interest on the students’ learning motivation is 45.5%, the rest is influenced by other variables. The YouTube videos were able to predict the students’ learning interest of 0.093 with low criteria whereas the YouTube videos and the learning interest were able to predict their learning motivation of 0.327 with moderate criteria. In general, this study shows that YouTube videos had a significant positive effect on the students’ learning interest and motivation in online mathematics learning.Keywords: Structural Equation Modeling; YouTube; Learning Interest; Learning Motivation ABSTRAKMinat dan motivasi belajar merupakan faktor-faktor yang dapat mempengaruhi hasil belajar. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan YouTube terhadap minat dan motivasi belajar matematika mahasiswa Program Studi Tadris Matematika Universitas Prof. K.H. Saifuddin Zuhri Purwokerto dengan menggunakan metode Structural Equation Modeling-Partial Least Square (SEM-PLS). Variabel-variabel yang digunakan dalam penelitian ini merupakan variabel-variabel laten dengan jumlah sampel yang digunakan adalah sebanyak 160 sampel. Dilakukan analisis dengan menggunakan software SmartPLS 3.0 dan didapatkan kesimpulan bahwa penggunaan YouTube berpengaruh positif langsung terhadap minat belajar secara signifikan (p value=0.000 0.05) dimana koefisien jalur sebesar 0.415, penggunaan YouTube berpengaruh positif langsung terhadap motivasi belajar secara signifikan (p value=0.000 0.05) dimana koefisien jalur sebesar 0.260, minat belajar berpengaruh positif langsung terhadap motivasi belajar secara signifikan (p value=0.000 0.05) dimana koefisien jalur sebesar 0.529 dan penggunaan YouTube berpengaruh positif tidak langsung terhadap motivasi belajar melalui minat belajar secara signifikan (p value=0.000 0.05) dimana koefisien jalur sebesar 0.220. Selanjutnya, dapat diketahui pula bahwa pengaruh total penggunaan YouTube terhadap motivasi belajar signifikan (p value=0.000 0.05) dimana koefisien jalur sebesar 0.480. Pengaruh penggunaan Youtube terhadap minat belajar adalah sebesar 16.7%, sisanya dipengaruhi oleh variabel lain dan pengaruh penggunaan Youtube dan minat belajar terhadap motivasi belajar adalah sebesar 45.5% dan sisanya dipengaruhi oleh variabel lain. Penggunaan YouTube mampu memprediksi minat belajar sebesar 0.093 dengan kriteria rendah dan penggunaan YouTube dan minat belajar mampu memprediksi motivasi belajar sebesar 0.327 dengan kriteria sedang. Secara umum, penelitian ini menunjukkan bahwa penggunaan YouTube akan berpengaruh positif signifikan terhadap minat dan motivasi peserta didik dalam mengikuti pembelajaran matematika secara daring.Kata Kunci: Structural Equation Modeling; Penggunaan YouTube; Minat Belajar; Motivasi Belajar